Mentoring to Support Family Volunteer Coordinators - Pomarańska, Renata (Studia Warmińskie, 2024)
Mentoring as a way to support family volunteering coordinators in fulfilling their various roles. It presents the specificity of family volunteering, which is particularly related to the minors of volunteers, which requires appropriate formal and legal activities. Attention was also paid to the family dimension of volunteering and some tasks that could be carried out by families within it were identified. Finally, the focus was on mentoring as a form of support which, due to its individual approach, can meet the diverse and non-standard professional needs of family volunteering coordinators.